Pengaruh Layanan Setoran Online USID (Ugt System Integrator Development) Gateway terhadap Kepuasan dan Loyalitas Nasabah di BMT UGT Sidogiri Cabang Klampis Kabupaten Bangkalan - Fuad Malik Romadhon; Muhaimin . (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2018)
The online deposit service implemented by BMT UGT Sidogiri Klampis Bangkalan Branch is an effort or strategic steps carried out by BMT UGT Sidogiri to attract customers and provide satisfaction and create customer loyalty. The purpose of this study was to determine the effect of implementing online deposit services on customer satisfaction and loyalty. The design of this study is quantitative research with data collection methods through questionnaire surveys or questionnaires that have been tested for validity and reliability. The sampling technique uses simple random sampling method with a total sample of 88 people who use online deposit services. Analysis using simple linear regression, the data is processed using the SPSS 19.0 program. The results of the study show that: (1) the description of quality online deposit services with a percentage of 87%. (2) An overview of customer satisfaction with online deposit services is quite good with a percentage of 84% (3) An overview of customer loyalty to online deposit services by 85% (4) There is a significant influence between online deposit services on customer satisfaction (5) There is a significant influence between online deposit services to customer loyalty. So based on these results, this deposit service should continue to be run and developed in order to continue to provide satisfaction and create customer loyalty that has a positive impact on the existence and progress of the company.